Review Essay: Recovering the Heritage of Past Research and Natural Resource Exploitation in Polar and Alpine Regions - Elzinga, Aant (Journal of Northern Studies, 2014)
Review of: Lars Andersson (ed.), Sarek, Arktis och akademisk vardag. En bok om geografen Axel Hamberg [‘Sarek, the High Arctic and academic everday life. A book about the geographer Axel Hamberg’] (Skrifter rörande Uppsala Universitet, Serie C, Organisation och Historia 94), Uppsala: Acta Universitatis Upsaliensis 2012, ISBN 9789155482541, 366 pp.; Susan Barr, David Newman & Greg Nesteroff, Ernest Mansfield (1862–1924). “Gold—or I’m a Dutchman!”, Trondheim: Akademika Publishing 2012, ISBN 9788232100200, 192 pp.